SPACE SEARCH FOR MINOR CROWDING CASES WITH EXPANSION PLATE IN PATIENTS WITH A HISTORY OF ANTIDEPRESSANT DRUG CONSUMPTION - Puspitarini Nindya Wardana; Yely Okta Mariza (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2023)
Introduction: Gaining space in malocclusion cases using expansion plate removable orthodontic appliances. Depression is a mental health disorder that is treated with antidepressants. There is a correlation between a history of long-term antidepressant medication use and orthodontic treatment. Case: A 21-year-old female patient with a history of antidepressant medication complained of slightly advanced maxillary front teeth and crowded mandibular front teeth. Clinical examination revealed the first permanent molar relation Angle Class I modified Dewey type 2 malocclusion with malposition of individual teeth. Arch discrepancy analysis showed a space deficiency of 4 mm in the maxilla and 2.85 mm in the mandible. Case Management: The first stage used a removable orthodontic appliance for maxillary and mandibular expansion plates to obtain space deficiency. The expansion results showed that the maxillary dental arch was successfully expanded by 4.52 mm and the mandibular by 4 mm. Discussion: The slow-type expansion plate functions to expand the dental arch. Conclusion and Suggestion: Expansion plate removable orthodontic treatment effectively gains space in patients with a history of antidepressant drug use. Patients' cooperativeness in wearing the appliance influences the expansion plate removable orthodontic appliance treatment result.